2017
DOI: 10.1021/acs.cgd.7b01035
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Aromatic Residues in Amyloids: A Survey of Protein Data Bank Crystallographic Data

Abstract: Aromatic–aromatic interactions have long been considered important in the self-assembly of amyloids. In spite of their importance, aromatic amino acids are not detected in every amyloid. In the present study, the occurrence and geometry of these interactions were analyzed for the amyloid structures found in the Protein Data Bank. The data confirm that aromatic amino acids are not crucial for amyloid fibril formation. In fact, aromatic–aliphatic interactions are more frequent than the aromatic–aromatic interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…[29,57] Recently, the single amino acid tyrosine has been shown to self-assemble into cross-β-like fibers through hydrogen bonding and π-π stacking, and the fibrils were shown to mediate the aggregation of proteins through amyloid crossseeding, illustrating the importance of tyrosine residues in controlling the structure and function of proteins. There have been reports on specific local arrangements of sequences that prefer certain secondary structures, e.g., residues that strongly prefer the N-terminal and N+1 positions at the start of an α-helix, general turn-inducing sequences, and repeat positions of the heptad leucine, which favors a coiled-coil or leucine zipper interaction.…”
Section: Tyrosine As a Structural Motifmentioning
confidence: 99%
See 2 more Smart Citations
“…[29,57] Recently, the single amino acid tyrosine has been shown to self-assemble into cross-β-like fibers through hydrogen bonding and π-π stacking, and the fibrils were shown to mediate the aggregation of proteins through amyloid crossseeding, illustrating the importance of tyrosine residues in controlling the structure and function of proteins. There have been reports on specific local arrangements of sequences that prefer certain secondary structures, e.g., residues that strongly prefer the N-terminal and N+1 positions at the start of an α-helix, general turn-inducing sequences, and repeat positions of the heptad leucine, which favors a coiled-coil or leucine zipper interaction.…”
Section: Tyrosine As a Structural Motifmentioning
confidence: 99%
“…The PCET process couples longdistance electron transfer from the active centers of enzymes and short-distance proton transfer to the surrounding bases. [57] Copyright 2017, American Chemical Society. As shown in the figure, the pK a value of every tyrosine oxidation pathway is in the range of 10 to −2, meaning that at most pH values, the oxidation of tyrosine is coupled to proton transfer.…”
Section: Proton-coupled Electron Transfer Of Tyrosinementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that valine, isoleucine and alanine have β sheet propensity due to their hydrophobicity and hydrogen bonding characteristics (Han et al, 2011 ; Cui et al, 2014 ). Whereas formation of direct π-π interactions involving phenylalanine do not seem to be important in promoting amyloid aggregation (Stankovic et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…These systems also attracted a lot of attention due to the pieces of evidence of proton transfer and proton tunneling . On the other hand, benzene and its derivatives undergo stacking interactions, which are particularly relevant in living organisms, but are also significant for crystal packing . We have thus chosen the BA as the smallest representative of aromatic carboxylic acids for theoretical analysis of noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%